What's Eating You? Cutaneous Myiasis (Wohlfahrtia magnifica) - Yildirim, Inci; Ceyhan, Mehmet; Cengiz, Ali Bulent; Saki, Cem Ecmel; Ozer, Edip; Beken, Serdar; Cilsal, Ermal (Quadrant Healthcom Inc, 2008)
[Abstract Not Available]
Keywords: Returning Traveler; Sarcophagidae; Schiner; Diptera